2011
DOI: 10.4317/medoral.16.e110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three prophylaxis methods on surface roughness of giomer

Abstract: Objectives: Plaque and stains are removed by prophylaxis methods from tooth surfaces. Since prophylaxis methods can have a detrimental effect on the surface finish of restorations, the aim of this in vitro study was to investigate the effect of three prophylaxis methods, including pumice with rubber cup, pumice with brush, and air-powder polishing device (APD) on the surface roughness of giomer. Study design: Sixty four cylindrical giomer (Beautifil II, Shofu) samples with a diameter of 6 mm and a height of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 9 publications
(12 reference statements)
0
21
0
7
Order By: Relevance
“…The stylus tip radius of AFM is smaller than SP, therefore, AFM has better spatial resolution providing more accurate roughness measurement [15,29]. Also, AFM can provide 3D topographic images, and suitability for qualitative and quantitative comparison of surface texture and roughness [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…The stylus tip radius of AFM is smaller than SP, therefore, AFM has better spatial resolution providing more accurate roughness measurement [15,29]. Also, AFM can provide 3D topographic images, and suitability for qualitative and quantitative comparison of surface texture and roughness [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…İçerisindeki PRG doldurucular, nemli siliköz jel oluşturmak için su varlığında fluoroaluminosilikat cam ile poliakrilik asidin asit-baz reaksiyonu sonucu meydana gelmektedir ve PRG doldurucular, önceden tepkimeye girmiş hidrojelden ligand değişimi sonucu hızlı flor salınımını teşvik etmektedir. [8][9][10] Materyalin bu özellikleri, çocuk diş hekimliğinde kullanımını gündeme getirmektedir.…”
Section: Discussionunclassified
“…İçerisinde önceden tepkimeye girmiş cam iyonomer [pre-reacted glass ionomer (PRG)] partikülleri bulunan giomerlerin, asitleme ve yıkama gerektirmediği için uygulama basamaklarını kısalttığı ve sürmekte olan dişlerde kullanım kolaylığı sağlayacağı ileri sürülmüştür. [8][9][10] Erişilebilir kaynaklarda, piyasaya yeni sürülen bu materyallerin başarısını değerlendiren in vitro çalışmalar sınırlı düzeyde olup, in vivo koşullarda bu materyallerin nem izolasyonunun zor olduğu dişlerde fissür örtücü olarak karşılaştırıldığı bir ça-lışmaya rastlanmamıştır. 9,11,12 Bu çalışmada, sürmekte olan daimi birinci büyük azı dişlere uygulanan giomer içerikli, hidrofilik ve hidrofobik yapıdaki rezin içerikli fissür ör-tücülerin, dişlerin oklüzyona geldikleri döneme kadar retansiyon açısından karşılaştırılması amaç-lanmıştır.…”
Section: Sürmekte Olan Daimi Birinci Büyük Azı Dişlereunclassified
“…Kimyai et al observed that the use of air-powder polishing device prophylaxis exerted the most detrimental effects on the surface of Giomer, resulting in an increased surface roughness [7]. …”
Section: Introductionmentioning
confidence: 99%